Losing legs and walking hard: effects of autotomy and different substrates in the locomotion of harvestmen in the genus Prionostemma - Dominguez, M (2016)
We thank A.G. Farji-Brener, F. Chinchilla, and G. Barrantes for their assistance in the design, analysis and interpretation of this project. E. Triana provided great suggestions to improve the project, as well as field assistance. We thank the Organization for Tropical Studies and Las Cruces Biological Station for providing housing, logistics, transportation and financial support during this project. V.R. Townsend, Jr., Joel Wixson, Elizabeth C. Braun, and two anonymous reviewers provided useful comments to improve this project. The Biology Department of the UPR at Rio Piedras provided financial support to CF. The Universidad de Antioquia, Colombia provided financial support to DG-R, and the Center For Conservation Education and Sustainability, Smithsonian Conservation Biology Institute and CONCYTEC for the financial support to FC-R.